Comparison of perioperative outcomes in patients with uncomplicated and complicated cholelithiasis - Bohara, Tanka Prasad; Regmee, Sujan; Laudari, Uttam; Shrestha, Alok; Joshi, Mukund Raj (Journal of Kathmandu Medical College, 2018)
Background: Cholelithiasis is a common disease managed by surgeons. The patient may present with asymptomatic incidentally detected cholelithiasis, uncomplicated symptomatic cholelithiasis or complicated symptomatic cholelithiasis. The perioperative outcome varies in patients with symptomatic uncomplicated and complicated disease. Objectives: To compare the perioperative outcomes between patients with uncomplicated and complicated cholelithiasis. Methodology: A prospective analytical study was conducted among all the patients undergoing elective laparoscopic cholecystectomy during the study period. The patients were categorized into two groups, uncomplicated and complicated. The comparison was done among these groups in terms of length of hospital stay, operative duration, and post-operative complications. Results: Total of 107 patients 22(20.56%) males and 85(79.43%) females were included in the study. 83(77.57%) were uncomplicated and 24(22.42%) were complicated cases. The average length of the hospital was 2.33 vs 6 days (p-value